Kriteria ruang publik Kalijodo pendukung aksesibilitas dan peningkatan aktivitas (ARTEKS : Jurnal Teknik Arsitektur, 2018)
Public space is a place for social, economic and culture activity. Besides green open spaces, there are a lot of space along the river that have potential issues to be created as a public space. In fact, number of riversides are filled by slum area and there is no public space along the riparian. This research focused on the determining the chriterias of public space that support connectivity and incilining the number of activities. Theory that applied for this research is A Guide to Riverfront Development by Charles A. McLaren amd Public Space principle by Stephen Carr and Carmona. Kalijodo is one of the public spaces that will be studied because of its position faced in front of the river. Based on those theories, there are chitrerias that will be used to analyse the study casem which are comfort, activity, sociability, and more focus on access, including pedestrian access point, type and distribution of universal access and pedestrian priority. The result of this research could be summarised that physical access are attained by stairs and bridge that connect from river. Eventhough, Kalijodo must concern about visual access, addition of specific program to spread the activities and support by dense of vegetation to reach comfort.
Keywords: activity; accessibility; public space; riverside